Mechanical Analysis of Serpentinite rock in Indrapuri, Tangse, and Beutong - Hasma Sarah; Fadhli Syamsudin; Lono Satrio (PSI-Aceh, 2012)
Aceh is one of province that has abundant natural resources, which consist of natural resources which can be renewed or not renewed. With the increasing human population, especially in Indonesia, resulting in increasing human needs of various sectors, particularly in the construction sector. In the development activities required a lot of materials-minerals, such as sandstone, limestone, serpentinite rock which serves for a variety of needs in development activities. In District Indrapuri (Aceh Besar Regency), Tangse (Pidie Regency), and Beutong (Nagan Raya Regency) finding of the serpentinite rock is abundance. Meanwhile, in line with the rapid physical development in Aceh and its surroundings, then the needs of rock as building materials will increase as well. Research done by physical properties (specific gravity, absorption, porosity), and mechanical properties (testing compressive strength, wear/abrassion) of serpentinite rock to determine its quality as a building material. The results show that the serpentinite rock contained in District Indrapuri, Tangse, and Beutong for the building according SII 0378-80 is qualified for the foundation, curb stones, and ornamental stones or paste stones.